Learning in action a guide to putting the learning organization to work - Garvin, David A. (Harvard Business School Press, 2000)
"Most managers today understand the value of building a learning organization. Their goal is to leverage knowledge and make it a key corporate asset, yet they remain uncertain about how best to get started. What they lack are guidelines and tools that transform abstract theory - the learning organization as an ideal - into hands-on implementations. For the first time in Learning in Action, David Garvin helps managers make the leap from theory to proven practice." "Garvin argues that at the heart of organizational learning lies a set of processes that can be designed, deployed, and led."--Jacket